2014
DOI: 10.1590/0103-9016-2013-0388
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic evaluation of 'Bordô' grapevine (Ives) clones

Abstract: 'Bordô' grapevines (Vitis labrusca) have great relevance to viticulture due to the quality they can impart to wines and juices. However, this cultivar has high variation in yield, ranging from 6 to 11 t ha ), the adoption of more productive clones can generate an increase in yield of around 38 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(13 reference statements)
2
6
0
1
Order By: Relevance
“…However, it is worth noting that, among the 11 evaluated genotypes in the present study, the most productive were genotypes G13 with 38.2 t ha -1 (22.9 kg/ plant), G16 with 37.06 t ha -1 (22.2 kg/plant), G19 with 35.4 t ha -1 (21.1 kg/plant) and G08 with 34.7 t ha -1 (20.8 kg/ plant) p < 0.05 (Table 1). The cultivation of the same genotypes, evaluated in the present study, was also reported by Miotto et al (2014), where the G13 genotype proved to be the most productive (14.9 t ha -1 ) in Caldas-MG, in the south of Minas Gerais state, although the plants were conducted in a spreading system and were from the third to the fifth year of cultivation on average. High mean estimates, between 34.1 to 38.1 t ha -1 were also observed by Brighenti et al (2018), with genotypes G08, G16, G19 and G13 and proved to be the most productive, in the sixth year and in the same cultivation location.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…However, it is worth noting that, among the 11 evaluated genotypes in the present study, the most productive were genotypes G13 with 38.2 t ha -1 (22.9 kg/ plant), G16 with 37.06 t ha -1 (22.2 kg/plant), G19 with 35.4 t ha -1 (21.1 kg/plant) and G08 with 34.7 t ha -1 (20.8 kg/ plant) p < 0.05 (Table 1). The cultivation of the same genotypes, evaluated in the present study, was also reported by Miotto et al (2014), where the G13 genotype proved to be the most productive (14.9 t ha -1 ) in Caldas-MG, in the south of Minas Gerais state, although the plants were conducted in a spreading system and were from the third to the fifth year of cultivation on average. High mean estimates, between 34.1 to 38.1 t ha -1 were also observed by Brighenti et al (2018), with genotypes G08, G16, G19 and G13 and proved to be the most productive, in the sixth year and in the same cultivation location.…”
Section: Resultssupporting
confidence: 81%
“…High mean estimates, between 34.1 to 38.1 t ha -1 were also observed by Brighenti et al (2018), with genotypes G08, G16, G19 and G13 and proved to be the most productive, in the sixth year and in the same cultivation location. An important factor to be noted is that, among the most productive genotypes, in the present study as well as those reported by Miotto et al (2014) and Brighenti et al (2018), refer to the cultivars 'Paco' (G13) and 'Bocaina' Rev. Ceres, Viçosa, v. 68, n.4, p. 310-318, jul/aug, 2021 (G16).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…No entanto, via de regra, a maturação da Bordô ocorre em períodos chuvosos nos estados do sul e sudeste brasileiro, prejudicando a qualidade das uvas, e por esta razão não atingem uma relação de açúcar e acidez suficiente para elaboração de um produto de qualidade, prejudicando por vezes o enquadramento do suco à legislação vigente (Chiarotti et al, 2011). Outro problema enfrentado em relação ao cultivo de Bordô é a oscilação na produção devido a distúrbios fisiológicos que prejudicam a do Rio do Peixe-SC Bender, A. et frutificação, reduzindo significativamente a produção em determinadas safras (Miotto et al, 2014;Castilhos et al, 2016).…”
Section: Introductionunclassified